The influence of internship training experience on Kenyan and Ugandan doctors' career intentions and decisions: a qualitative study - Zhao, Y; Mbuthia, D; Ankomisyani, DS; Blacklock, C; Gathara, D; Molyneux, S; Nicodemo, C; Okello, TR; Rutebemberwa, E; Tweheyo, R; English, M (Taylor and Francis, 2023)
Background: Medical internship is a key period for doctors’ individual career planning and also a transition period for the broader labour market. Objectives: We aimed to understand the complex set of factors influencing the career intentions and decisions of junior doctors, post-internship in Kenya and Uganda. Methods: We conducted semi-structured interviews with 54 junior medical officers and 14 consultants to understand doctors’ internship experiences and subsequent employment experiences. We analysed the data using a mix of a direct content approach, informed by an internship experience and career intentions framework developed primarily from high-income country literature, alongside a more inductive thematic analysis. Results: Echoing the internship experience and career intentions framework, we found that clinical exposure during internship, work–life balance, aspects of workplace culture such as relationships with consultants and other team members, and concerns over future job security and professional development all influenced Kenyan and Ugandan doctors’ career preferences. Additionally, we added a new category to the framework to reflect our finding that interns might want to ‘fill a health system gap’ when they choose their future careers, based on what they witness as interns. However, often career intentions did not match career and employment decisions due to specific contextual factors, most importantly a shortage of job opportunities. Conclusion: We have shown how internship experiences shape medical doctors’ career intentions in Kenya and Uganda and highlighted the importance of job availability and context in influencing doctors’ career choices.